Pilotní, dvojitě slepá, placebem kontrolovaná studie s megestrol acetátem u dialyzovaných seniorů s kachexií - Yeh, S. S; Marandi, M; Thode, H. C; Levine, D. M; Parker, T; Dixon, T; Schuster, M. W (Postgraduální nefrologie, 2010)
OBJECTIVE: We examined the effects of megestrol acetate versus placebo and progressive resistance physical exercise on weight, lean muscle mass, quality of life, ability to exercise, proinflammatory cytokines, and anti-inflammatory cytokines, and their correlations with one another. DESIGN: We organized a prospective 20-week, randomized, double-blind, placebo-controlled pilot trial of hemodialysis patients. SETTING: This study took place at the Outpatient Unit of the Northport Veteran Affairs Medical Center. SUBJECTS: We studied nine male hemodialysis patients who had two or more of the following: albumin level <4.0 g/dL, total cholesterol <150 mg/dL, protein catabolic rate <0.8 g/kg/day, and predialysis serum urea nitrogen <60 mg/dL. Their ages were 50 to 83 years. Two were diabetic, and seven were nondiabetic. INTERVENTIONS: Interventions included megestrol acetate (MA) or placebo 800 mg oral daily for 20 weeks, along with weight resistance physical therapy with weights twice a week before dialysis. Patients were followed prospectively for an additional 4 weeks. MAIN OUTCOME MEASUREMENTS: Weight, body composition, activities of daily living, ability to exercise, and plasma cytokine levels were measured. RESULTS: At 24 weeks, the MA group had a statistically significant weight gain (11.1-pound increase vs. 1.5-pound decrease for the placebo group, P = .018), body fat gain (6.2-pound increase vs. a 0.4-pound decrease for the placebo group, P = .044) and fat-free mass gain (5-pound increase vs. a 1.2-pound decrease in the placebo group). The MA group also had a greater tendency toward increased appetite and sense of well-being. The MA group showed a greater improvement in ability to exercise (mean change in rate of perceived exertion (RPE), 4.7) vs. the placebo group (mean change in RPE vs. 0.5, P = .02). Elevated cytokine levels were evident at baseline in both groups. In all patients, increases in weight, fat-free mass, sense of well-being, appetite, and ability to exercise were negatively correlated with tumor necrosis factor receptor subunit p75 (P < .05). There was a trend toward all of these parameters to be negatively correlated with tumor necrosis factor receptor subunit p55, although only sense of well-being was statistically significant (P < .05). CONCLUSION: In a pilot trial in dialysis patients, MA showed significant benefits in improving weight and ability to exercise. Cytokine changes were correlated with weight gains and increases in fat-free mass.
Keywords: financování organizované; Randomized Controlled Trials as Topic; cholesterol; Cytokines; Renal Dialysis; hmotnostní přírůstek; placebo; dialýza ledvin; Weight Gain; Resistance Training; podjednotky proteinů; cytokiny; Appetite Stimulants; lidé; dvojitá slepá metoda; kachexie; Activities of Daily Living; cvičení; Pilot Projects; pilotní projekty; dusík močoviny v krvi; Aged, 80 and over; megestrolacetát; sérový albumin; Cholesterol; Financing, Organized; Cachexia; tělesná hmotnost; činnosti denního života; prospektivní studie; Double-Blind Method; Male; Receptors, Tumor Necrosis Factor; složení těla; Aged; Prospective Studies; Blood Urea Nitrogen; Placebos; Protein Subunits; randomizované kontrolované studie jako téma; Body Weight; Body Composition; Serum Albumin; lidé středního věku; receptory TNF; senioři nad 80 let; Megestrol Acetate; senioři; mužské pohlaví; chuťová stimulancia; Exercise; Middle Aged; odporový trénink; Humans